The Referential Uses of Demonstratives in Kerinci Malay, Indonesia - Ernanda Ernanda (JURNAL ARBITRER, 2020)
Demonstratives are pervasive and ubiquitous in every human language. This study explores further evidence from Kerinci, a Malayic sub-variety spoken in Sumatra, Indonesia. It highlights the referential uses of the Kerinci proximal demonstratives ineh/neh 'this' and the distal demonstrative itoh/toh 'that'. It is based on a corpus containing eight hours of recordings. The basic indexical functions of demonstratives within the referential domain are sketched from three perspectives, namely syntactic contexts, deictic expressions, and pragmatic uses. In light of the evidence presented, this study supports the most accepted principle that demonstratives are universal. However, this research also suggests that the form, use, and meaning of the Kerinci demonstratives are language-specific as presented in this paper.